2022
DOI: 10.3390/electronics11071042
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal Aging Model of Li-Ion Batteries for Vehicle-to-Grid Services Evaluation

Abstract: The growing interest in Electrical Vehicles (EVs) opens new possibilities in the use of Li-ion batteries in order to provide ancillary grid services while they are plugged to recharging stations. Indeed, Vehicle-to-Grid (V2G), Vehicle-to-Building (V2B), Vehicle-to-Home (V2H) as well as Vehicle-to-Vehicle (V2V) services can be carried out depending on the particular installation and on the connection to the distribution grid of the considered recharging station. Even if these are interesting and challenging opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The frequency regulation or light peak shaving V2G operations with smaller SOC changes is usually believed to cause less deterioration to the batteries [37], while it is argued in [38] that, after the equal Ah throughput, capacity fade is higher for frequency service due to higher SOCs than peak shaving. A similar conclusion is derived from [39] that Ah throughput almost doubled from 120,000 Ah to 230,000 Ah with only 20% lifetime reduction. Cycling aging is usually regarded as the main concern involving degradation cost in grid applications [40], while in [41] calendar aging is modeled as the main degradation function for common EV charging profiles.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The frequency regulation or light peak shaving V2G operations with smaller SOC changes is usually believed to cause less deterioration to the batteries [37], while it is argued in [38] that, after the equal Ah throughput, capacity fade is higher for frequency service due to higher SOCs than peak shaving. A similar conclusion is derived from [39] that Ah throughput almost doubled from 120,000 Ah to 230,000 Ah with only 20% lifetime reduction. Cycling aging is usually regarded as the main concern involving degradation cost in grid applications [40], while in [41] calendar aging is modeled as the main degradation function for common EV charging profiles.…”
Section: Introductionsupporting
confidence: 82%
“…The research in [34] found that C-rate will have little effect on aging results if the temperature is maintained strictly constant. It is observed in [39] that at 20 • C, cells cycled under 1 C and 2 C decay slower than those under 0.5 C. Additionally, the rise of temperature from 20 to 34 • C has improved the battery life under several high C-rates. This phenomenon may be explained by the improvement of calendar aging under high C-rates [28].…”
Section: Different Dod and C-ratementioning
confidence: 99%
“…The main advantages of the proposed system are the fact that the realized wireless accelerometers are low cost, compact, and easy to install in the point of interest on the structure. These sensors are autonomous from an energetic point of view, thanks to the sensor's low-power consumption and the use of a mini-PV panel to recharge the lithium-polymer (Li-Po) battery when an energy excess is produced [35]. This way, the realized system can be permanently mounted on the structure during its entire service life and the wireless communication helps avoid the use of any cables between sensors and the acquisition part.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers provide battery aging models developed for several applications, generally applied to operating conditions assessed in relation to specific sizing and integration conditions. For instance, [15] focuses on a Li−ion battery pack, proposing a semiempirical electrothermal aging model that accounts for calendar and cycle aging at different C−rates and temperatures, also considering vehicle−to−grid (V2G) services. Nevertheless, the model does not take into account any experiment based on the actual operating BEV mode, such as the driving cycle.…”
Section: Introductionmentioning
confidence: 99%